Pulmonary Hydatidosis with parahydatio pleural complications: empyema anrd serofibrinous pleuresy. - Aliano, Artigas; Belloso (h), Rogelio; Soto Cordano, José (Cirugía del Uruguay, 1977)
A case of pulmonary hydatidosis complicated with pleuresy and parahydatid empyema leads the author to insist on diagnostica! difficulties of hydatidosis, especially in cases of complicated forms and most particularly in the less frequent types. Pathogeny of these complications is analyzed and the importance and therapeutic value of aggressive early surgery is stressed.